SECTORAL EQUITY MARKET RESPONSES TO THE COVID-19 PANDEMIC IN INDIA: A PANEL DATA ANALYSIS OF EPIDEMIOLOGICAL AND POLICY VARIABLES - Nandi, Archan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose: This study investigates the impact of the COVID-19 pandemic on sectoral equity returns in India, incorporating both epidemiological indicators (case growth and death toll) and government interventions (lockdown and vaccination). It also evaluates the influence of key macroeconomic variables during this period of heightened uncertainty. Methodology: Using weekly panel data from January 2019 to December 2021 across seven Nifty sector indices – Pharma, FMCG, IT, Auto, Bank, Realty, and Energy, the study employs a fixed effects panel regression framework. The dependent variable is the log return of each sector. Explanatory variables include log-transformed COVID-19 cases and deaths, lockdown and vaccine dummies, exchange rate, crude oil price, repo rate, India VIX, and CPI inflation. Diagnostics such as multicollinearity (VIF), correlation matrix, and normality were conducted using SPSS to ensure model robustness. Findings: A statistically significant negative relationship was found between COVID-19 case growth and sectoral returns. In contrast, reported deaths exhibited a positive association, possibly reflecting investor expectations of policy relief. Lockdown announcements had a positive and significant effect, while the impact of vaccination remained statistically inconclusive. Macroeconomic variables were largely insignificant. Sector-wise regressions revealed heterogeneity in responses, with Pharma and IT reacting more strongly than Realty or FMCG. Value: The study contributes to the growing literature on pandemic-driven financial dynamics by integrating weekly epidemiological and policy data into a sectoral panel framework. It offers relevant insights for investors, regulators, and policy planners in emerging markets.